2022
DOI: 10.1038/s41467-022-30227-5
|View full text |Cite
|
Sign up to set email alerts
|

Serum metabolome associated with severity of acute traumatic brain injury

Abstract: Complex metabolic disruption is a crucial aspect of the pathophysiology of traumatic brain injury (TBI). Associations between this and systemic metabolism and their potential prognostic value are poorly understood. Here, we aimed to describe the serum metabolome (including lipidome) associated with acute TBI within 24 h post-injury, and its relationship to severity of injury and patient outcome. We performed a comprehensive metabolomics study in a cohort of 716 patients with TBI and non-TBI reference patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 67 publications
3
43
0
Order By: Relevance
“…As researches conducted by Wang and colleagues, they performed transcriptomics or in situ imaging using tumor tissues to illustrate the underlying mechanism, validating that the dysregulated lipids found in blood was caused by dysregulated metabolic status in corresponding tumor tissues (Wang et al, 2022). In the metabolomic research conducted by Chen et al (2022) and Talmor-Barkan et al (2022), metagenome sequencing-based gut microbiome analyses of paired fecal samples were used to illustrate the origin of the dysregulated metabolite biomarkers in serum, proving the true association between the found diagnostic biomarkers and the diseases. Xiao et al (2022) performed experiments on patient-derived organoid and xenograft models to illustrate the underlying mechanism of the found dysregulated metabolome in triple-negative breast cancer.…”
Section: Important Issues Need To Be Concerned When Employing Metabol...mentioning
confidence: 90%
See 2 more Smart Citations
“…As researches conducted by Wang and colleagues, they performed transcriptomics or in situ imaging using tumor tissues to illustrate the underlying mechanism, validating that the dysregulated lipids found in blood was caused by dysregulated metabolic status in corresponding tumor tissues (Wang et al, 2022). In the metabolomic research conducted by Chen et al (2022) and Talmor-Barkan et al (2022), metagenome sequencing-based gut microbiome analyses of paired fecal samples were used to illustrate the origin of the dysregulated metabolite biomarkers in serum, proving the true association between the found diagnostic biomarkers and the diseases. Xiao et al (2022) performed experiments on patient-derived organoid and xenograft models to illustrate the underlying mechanism of the found dysregulated metabolome in triple-negative breast cancer.…”
Section: Important Issues Need To Be Concerned When Employing Metabol...mentioning
confidence: 90%
“…Chen et al (2022) explored serum metabolome of patients with colorectal cancer or adenoma, and successfully found eight gut microbiomeassociated serum metabolites that could accurately discriminate patients from normal individuals. Talmor-Barkan et al (2022) performed serum metabolomics for 199 patients with acute coronary syndrome, revealing personalized risk factors for coronary artery disease. These researches focused on blood or urine-derived samples for biomarker development, taking advantage of the non-invasive and side effect-free features of blood tests, thus have great potential to be employed for largescale screening in populations with high risks or in regular physical examination for normal population.…”
Section: Metabolomics For Early Detection Largescale Screening or Dia...mentioning
confidence: 99%
See 1 more Smart Citation
“…For data preprocessing, the raw data files were converted to a .mzml file using Bruker compass data analysis 5.1. The preprocessing was performed in MZmine2 (version 2.53) according to Thomas et al [ 19 ]. Briefly, centroid mass detection was performed, followed by ADAP chromatogram builder, chromatogram deconvolution (local minimum search), and isotopic peaks grouper with join aligner.…”
Section: Methodsmentioning
confidence: 99%
“… 672 The study carried out by Thomas et al highlighted pathophysiological mechanisms from serum metabolome, and demonstrated metabolic disruption of choline phospholipids as among the strongest predictors were associated with severity of traumatic brain injury patients. 673 Furthermore, a study proven palmitic acid is a key metabolite as promising therapeutic target, which accelerates cellular senescence by producing living oxygen in kawasaki disease. 674 …”
Section: Functional Targetmentioning
confidence: 99%